Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai di Kecamatan Medan Satria Kota Bekasi - Sanitya Silvia Rahmawati (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine how workload and work environment affect employee performance at the Medan Satria Subdistrict Office, Bekasi City. This type of research uses a quantitative approach. The population in this study were 49 respondents with the sampling technique using saturated sampling technique. Data collection using primary data and secondary data. The data analysis technique uses the help of SPSS 25.00 by conducting data quality tests, classical assumption tests, multiple linear regression tests, hypothesis testing, and the coefficient of determination (R2) test. The results showed that partially workload affects employee performance, partially work environment affects employee performance and simultaneously workload and work environment affect employee performance Furthermore, the results of the coefficient of determination (R2) test indicate that workload and work environment have an influence on employee performance by 40% and the remaining 60% is influenced by,other variables not examined in this study.